PEMANFAATAN DATA CITRA ALOS UNTUK PEMETAAN LAHAN SAWAH: STUDI KASUS DI BEBERAPA LOKASI DI JAWA - Nurwadjedi, Nurwadjedi; Poniman, A (GEOMATIKA, 2009)
Problem of the rice field sustainability in Java as the national rice producer is mainly caused by rice field conversion into settlement and industrial areas. This phenomenon needs to be solved by making the policy of establishing standard land of rice field areas. This effort is, however, still facing the constraint of accurate and uptodate data availability. The limitation could be solved by mapping the rice fields using the optic satellite remote sensing data which has high spatial resolution, such as ALOS PRISM and AVNIR-2. It is believed that the use of ALOS PRISM and AVNIR-2 is not a good choice for mapping the rice fields using quantitative interpretation method which mainly relies on spectral reflectance values of objects on the earth because the rice field cover varies in close distance. For this reason, the qualitative interpretation method needs to be tested. The objective of this study is to assess the use of ALOS PRISM and AVNIR-2 for mapping the rice fields using visual interpretation. The results show that ALOS PRISM imagery can be used for mapping the rice fields at the optimum scale of 1: 5.000, while ALOS AVNIR-2 at 1:25.000. The rice field areas interpreted from ALOS PRISM and AVNIR-2 are smaller than that from Landsat 7 due to the generalization factor.Keywords: visual interpretation, spatial data, land conversion, generalizationÂ ABSTRAKÂ Permasalahan lahan sawah di Jawa sebagai penghasilpadi nasional disebabkan terutama oleh konversi lahan sawah ke perumahan dan industri. Fenomena ini perlu dipecahkan dengan kebijakan untuk menetapkan luasan lahan sawah standar. Namun usaha ini masih menghadapi masalah akurasi data dan ketersediaan data. Ini dapat diatasai dengan pemetaan lahan sawah dari satelit optis beresolusi tinggi seperti ALOS PRISM dan AVNIR-2. Dipercaya bahwa kedua sensor ini bukan pilihan yang tepat untuk pemetaan lahan sawah dengan metode kuantitatif yang bergantung pada nilai refletansi objek karena lahan sawah sangat bervariasi dari jarak dekat. Dengan alasan tersebut interpretasi kualitatif perlu diuji. Tujuan dari penelitian ini adalah mengkaji penggunaan ALOS PRISM dan AVNIR-2 untuk pemetaan lahan sawah dengan metode interpretasi visual. Hasilnya menunjukkan bahwa ALOS PRISM dapat digunakan untukpemetaan lahan sawah pada skala optimum 1:5.000, sedangkan ALOS AVNIR-2 pada skala 1:25.000. Area lahan sawah hasil interpretasi ALSO PRISM dan AVNIR-2 labih kecil dibandingkan hasil interpretasi Landsat 7 karena faktor generalisasi.Kata kunci: interpretasi visual, data spasial, konversi lahan, generalisasi.